Our Experience with Narrow-Band UVB for 15 Years: A Retrospective Study of 205 Patients (Annals of Medical Research, 2021)
Aim: Widely used in many indications in dermatology practice, narrow-band ultraviolet B is a kind of ultraviolet with a wavelength usually condensing at 312nm. Our aim in this study is to introduce our 15-year experience with narrow-band UVB on 205 patients.
Keywords: Mycosis Fungoides; Narrow Band UVB; Phototherapy; Psoriasis.